Nutrients for sugar beet production: soil-plant relationships - Draycott, A. P.; Christenson, D. R.; Christenson, D. R.; Draycott, A. P. (Wallingford :CABI Publishing, 2003)
This book provides an up-to-date review of research on sugarbeet nutrition, including topics not covered in a similar work published in the early 1970s, such as soil and plant analyses, organic farming, sustainability, satellite mapping and remote sensing. Chapter 1 provides an overview of sugarbeet production, the nutrient content and fertilizer requirements of sugarbeet, and yield responses to fertilizer application. The following 5 chapters include nutrient availability, nutrient uptake, nutrient transport, sources of fertilizer, fertilizer recommendations based on soil/foliar analysis, and effects of fertilizers on physiology and yield (chapter 2 for nitrogen; chapter 3 for phosphorus and sulfur; chapter 4 for potassium and sodium; chapter 5 for calcium and magnesium; and chapter 6 for boron, manganese, copper, zinc and iron). Chapter 7 focuses on nutrient deficiencies, whereas chapter 8 discusses organic manures and green manuring as sources of nutrients under organic farming. Chapter 9 reviews research on nutrient reserves and residual effects in crop rotations. Chapter 10 covers the effects of soil physical conditions on sugarbeet performance, whereas chapter 11 discusses the time, form and method of fertilizer application. Chapter 12 reviews the interactions between nutrients, water supply, pests and diseases, and agronomic practices. Chapter 13 discusses the effects of fertilizers on sugarbeet quality. Chapter 14 covers the nutrient requirements of fodder beet and the beet seed crop.
Keywords: FF005 - Field Crops, (New March 2000); FF007 - Forage and Fodder Crops, (New March 2000); FF040 - Plant Composition; FF060 - Plant Physiology and Biochemistry; FF061 - Plant Nutrition; FF100 - Plant Production; FF150 - Plant Cropping Systems; FF610 - Viral, Bacterial and Fungal Diseases of Plants, (New March 2000); FF620 - Plant Pests, (New March 2000); FF700 - Plant Disorders and Injuries (Not caused directly by Organisms); JJ300 - Soil Physics; JJ600 - Soil Fertility; JJ700 - Fertilizers and other Amendments; JJ800 - Soil Water Management (Irrigation and Drainage), (Revised June 2002); QQ050 - Crop Produce; QQ500 - Food Composition and Quality; XX100 - Animal Wastes; ZZ900 - Techniques and Methodology